Foreign direct investment, financial development and economic prosperity in major south Asian economies. (4th November 2020) - Sethi, Narayan; Das, Aurolipsa; Sahoo, Malayaranjan; Mohanty, Saileja; Bhujabal, Padmaja
Abstract : Purpose: This paper empirically examines the relationship between foreign direct investment, financial development and other macroeconomic variables like trade openness, domestic investment and labour force and that of GDP per capita in select South Asian countries, i.e. India, Sri Lanka and Pakistan for the period 1990–2018. Design/methodology/approach: The study uses various econometrics tools such as Pedroni, Kao and Johansen–Fisher panel cointegration test, Panel FMOLS and DOLS and Granger causality in order to analyse the long-run and short-run dynamics among the variables under consideration. Findings: The results of the panel data estimation techniques employed imply that there is a short-run causality running from GDP per capita to FDI and financial development, and results from FMOLS and DOLS indicate that FDI and financial development have positive impacts on GDP per capita in the countries under consideration. Originality/value: In this paper, we use a dynamic macroeconomic modelling framework to examine the effect of FDI and financial development on per capita income in three major south Asian economies, which are categorized as three Non-Least Developed Contracting States under the South Asian Free Trade Area (SAFTA), 2006, established with an aim to facilitate free trade among them. Considering the diversity of the level of growth experienced by these economies, the study uses appropriate panel regression techniques. Therefore, in addition to proper formulation of policies directed towards scaling up of export and import levels, the respective authorities should also take care that the political stability and institutional quality are maintained.